2022
DOI: 10.1111/jopy.12769
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dynamic personality theories in a continuous‐time framework: An illustration

Abstract: Personality psychology has traditionally focused on stable between-person differences. Yet, recent theoretical developments and empirical insights have led to a new conceptualization of personality as a dynamic system (e.g., Cybernetic Big Five Theory). Such dynamic systems comprise several components that need to be conceptually distinguished and mapped to a statistical model for estimation. In the current work, we illustrate how common components from these new dynamic personality theories may be implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 118 publications
2
9
0
Order By: Relevance
“…Our study adds that personality trait changes might even occur faster (across four months) during major life transitions. These findings emphasize the dynamic aspects of personality that have long been neglected in the field but currently attract attention (see Hecht et al, 2022). Our study provides a first, yet still somewhat indirect indication that novel insights into the dynamic aspects of personality can be obtained by combining trait with state measures.…”
Section: No Mean-level Personality Maturation During the Education-to...supporting
confidence: 61%
See 1 more Smart Citation
“…Our study adds that personality trait changes might even occur faster (across four months) during major life transitions. These findings emphasize the dynamic aspects of personality that have long been neglected in the field but currently attract attention (see Hecht et al, 2022). Our study provides a first, yet still somewhat indirect indication that novel insights into the dynamic aspects of personality can be obtained by combining trait with state measures.…”
Section: No Mean-level Personality Maturation During the Education-to...supporting
confidence: 61%
“…Instead of treating this individual variability in change as uninteresting noise, exploring its sources provides great potential to understand causal processes of personality change, as causal effects are heterogeneous (Bolger et al, 2019). This endeavor would greatly benefit from exploring sources of heterogeneity in both trait and state changes, which we found, to better understand the between-person differences (e.g., within-person variability) in within-person personality dynamics (Geukes et al, 2018;Hecht et al, 2022). In addition to individual factors, future research is needed to identify environmental demands (e.g., job requirements, workplace characteristics) that contribute to individual differences in personality change.…”
Section: Substantial Individual Variability In Personality Changementioning
confidence: 98%
“…Hence, previously found relations in between-person studies are likely to not pertain to the within-person level of longitudinal links between personality and achievement (see also e.g., Brose et al, Hamaker et al, 2015;Hübner et al, 2023): Here, we observed nonsignificant within-person links between personality and academic achievement, while the extant literature brims with findings of significant between-person associations between personality and academic achievement (e.g., Andersen et al, 2020;Poropat, 2009;von Stumm et al, 2011). Although the theoretical importance of within-person differences in personality is broadly recognized (e.g., Brandt et al, 2019;Hecht et al, 2022;Wrzus & Roberts, 2017), the respective empirical evidence base is just emerging. Our current results are a first step for contributing to this emerging evidence base for the links between personality and academic achievement.…”
Section: Discussionsupporting
confidence: 51%
“…Hence, previously found relations in between‐person studies are likely to not pertain to the within‐person level of longitudinal links between personality and achievement (see also e.g., Brose et al, 2020; Hamaker et al, 2015; Hübner et al, 2023): Here, we observed nonsignificant within‐person links between personality and academic achievement, while the extant literature brims with findings of significant between‐person associations between personality and academic achievement (e.g., Andersen et al, 2020; Poropat, 2009; von Stumm et al, 2011). Although the theoretical importance of within‐person differences in personality is broadly recognized (e.g., Brandt et al, 2019; Hecht et al, 2022; Wrzus & Roberts, 2017), the respective empirical evidence base is just emerging. Our current results are a first step for contributing to this emerging evidence base for the links between personality and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous time models, another approach to study within‐person reciprocal associations, have recently started to gain traction in psychology. Continuous time models easily integrate data from flexible longitudinal designs with unequally spaced measurement occasions, facilitate cross‐study comparisons, and help exploring the unfolding of cross‐lagged effects across different time intervals (Hecht et al, 2022; Hecht & Zitzmann, 2020). The latent curve model with structured residual (LCM‐SR, Curran et al, 2014) represents another alternative to model reciprocal within‐person relations.…”
Section: Discussionmentioning
confidence: 99%